(untitled) (International Journal of Engineering and Computer Science, 2017)
CBIR applies to techniques for retrieving similar images from image databases, based on automated feature extraction methods. In recent years, the medical imaging field has been grown and is generating a lot more interest in methods and tools, to control the analysis of medical images. CBIR for medical images has become a major necessity with the growing technological advancements. The content of an image have to be carefully extracted, classified with efficient techniques foe easy retrieval. Contents in an image can be of various forms like texture, color and shape etc of which is regarded as the most efficient metric. Medical images are usually fused, subject to high inconsistency and composed of different minor structures. So there is a necessity for feature extraction and classification of images for easy retrieval. There are various methods have been proposed for medical image retrieval system such as Shape Based Method, Texture Based Method, Continuous Feature Selection Method, Storage and access methods.